2015
DOI: 10.1007/s00256-015-2173-x
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy computed tomography of cruciate ligament injuries in acute knee trauma

Abstract: DECT is a usable method to evaluate ACL in acute knee trauma patients with rather good sensitivity and high specificity. GSI is generally a better evaluation protocol than bone removal or collagen-specific color mapping in the evaluation of cruciate ligaments and popliteus tendon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 15 publications
2
26
2
1
Order By: Relevance
“…Owing to its easy visualization of changes in HU values, CT color mapping has been applied clinically to assess bone remodeling, bone or soft tissue structure, and osseointegration to implant surfaces. [ 14 , 15 , 17 , 21 , 22 ] In the present study, the assessment of bone ongrowth on the surface of Ti-coated PEEK cages by CT color mapping had adequate inter- and intraobserver reliability. Moreover, even if the HU values decreased in a rectangular ROI in total, color mapping could easily detect bone ongrowth on the surface of the cage frame where the local increase in HU values occurred (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Owing to its easy visualization of changes in HU values, CT color mapping has been applied clinically to assess bone remodeling, bone or soft tissue structure, and osseointegration to implant surfaces. [ 14 , 15 , 17 , 21 , 22 ] In the present study, the assessment of bone ongrowth on the surface of Ti-coated PEEK cages by CT color mapping had adequate inter- and intraobserver reliability. Moreover, even if the HU values decreased in a rectangular ROI in total, color mapping could easily detect bone ongrowth on the surface of the cage frame where the local increase in HU values occurred (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Unfortunately, the thinner ligaments such as tibial collateral ligaments and patellar retinaculum were only poorly visualized. Peltola et al 60 performed a similar study in traumatic knee injuries and compared three different DECT analyses (monochromatic spectral images, bone removal images, and collagen-specific color mapping) in a single-source General Electric DECT scanner in complete ACL and posterior cruciate ligament tears. They also noted that the color mapping was least useful and that in most cases, monochromatic spectral images were superior, although, in some cases, bone removal was best.…”
Section: Tip 8: Collagen Analysismentioning
confidence: 99%
“…Although still at the research stage of development, several studies showed promising results for the evaluation of ligaments, in particular for evaluation of anterior cruciate liga-ment injuries. 73 Although MRI remains the gold standard for imaging cartilaginous structures, DECT may be an acceptable alternative technique when MRI is contraindicated or unavailable.…”
Section: Imaging Of Cartilaginous Structuresmentioning
confidence: 99%